Exploring genetic associations and drug targets for mitochondrial proteins and schizophrenia risk - Wenxi Sun; Ping Sun; Jin Li; Qun Yang; Qing Tian; Shiting Yuan; Xueying Zhang; Peng Chen; Chuanwei Li; Xiaobin Zhang (Schizophrenia)
Abstract Numerous observational studies have highlighted associations between mitochondrial dysfunction and schizophrenia (SCZ), yet the causal relationship remains elusive. This study aims to elucidate the causal link between mitochondria-associated proteins and SCZ. We used summary data from a genome-wide association study (GWAS) of 66 mitochondria-associated proteins in 3,301 individuals from Europe, as well as a GWAS on the large, multi-ethnic ancestry of SCZ, involving 76,755 cases and 243,649 controls. We conducted bidirectional two-sample Mendelian randomization (MR) analyses, with inverse variance weighting (IVW) as the primary method. To account for multi-directionality and ensure robustness, we included MR-Egger, weighted median (WM), weighted mode, and simple mode methods as supplementary sensitivity analyses. Moreover, we explored the GWAS catalog and the Drug-Gene Interaction Database (DGIdb) to identify and evaluate potential therapeutic targets. MR analysis revealed significant genetically determined causal associations between ETHE1 (OR: 1.06), SOD (OR: 0.97), CALU3 (OR: 1.03), and C1QBP (OR: 1.05) and SCZ. According to the reverse MR analysis, a causal relationship was shown between SCZ and CA5A (OR: 1.09), DLD (OR: 1. 08), AIF1 (OR: 0.93), SerRS (OR: 0.93) and MULA of NFKB1 (OR: 0.77). After conducting the gene-drug analysis, HRG, F12, GPLD1, C1R, BCHE, CFH, PON1, and CA5A were identified as promising therapeutic targets. This present study reveals a significant causal relationship between mitochondria-associated proteins and SCZ, offering valuable insights into the disease’s pathogenicity and identifying potential therapeutic targets for drug development.